AB0313 Short-Term Effects of Tnf Inhibitors on Bone Turnover Markers and Bone Mineral Density in Rheumatoid Arthritis. (15th July 2016) - Orsolini, G.; Adami, G.; Viapiana, O.; Idolazzi, L.; Fassio, A.; Vitiello, M.; Gatti, D.; Rossini, M.
Abstract : Background: TNFα inhibitors (TNFαI) exert positive effects on disease activity in rheumatoid arthritis (RA). Bone involvement is a major determinant of functional impairment in this disease. Objectives: Here we investigated the short-term effects of TNFαI therapy on bone metabolism and density. Methods: We studied 54 patients with RA starting a TNFI biologic drug, in whom any factor known to interfere with bone metabolism was excluded or rigorously accounted for. We measured at baseline and after 6 month therapy bone turnover markers (BTM): N-propeptide of type I collagen (P1NP), and bone alkaline phosphates (bAP) for bone formation and serum C-terminal telopeptide of type I collagen (CTX) for bone resorption. We also evaluated bone mineral density (BMD) at hip and lumbar by dual energy X ray absorptiometry (DEXA). Results: All bone markers rose significantly and these changes were not dependent on steroids dosage; a significant decrease in femoral neck BMD was also observed (see Table). Conclusions: These results indicate that TNFαI therapy in RA over 6 months is associated with an early increase in bone turnover and a decline in hip BMD. Disclosure of Interest: None declared